Studi Komparatif Pembelajaran Matematika Menggunakan Media Visual dan Media Benda Konkret Terhadap Hasil Belajar di Madrasah Ibtidaiyah - Fitri, Novida Aprilina Nisa; Deviansyah, Sefta (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2023)
This research aims to compare student learning outcomes in mathematics subjects using visual learning media and concrete object media. This research uses a classroom action research (PTK) design which is carried out in five cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The data collection technique used is an observation of teacher and student activities, tests, and field notes. The data collected in this research was analyzed using quantitative and qualitative analysis techniques. Based on the results of the analysis that has been described, there are differences in the learning outcomes of class I-B students who use concrete object media and class I-C students who use visual media in mathematics subjects. The learning outcomes of class I MIN 1 Kediri City students who use concrete object media are higher compared to students who use visual media.